Development of a 500mhz Reflectometer Using Stripline Coupler for Moisture Measurement of Oil Palm Fruits - Lee, Kim Yee (2004)
This thesis describes the development of a cost effective PC-based reflectometer for the determination of moisture content in oil palm fruits to gauge its degree of ripeness. The PC-controlled reflectometer which operates at 500 MHz consists of a stripline directional coupler, two diode detectors, a data acquisition card and two open-ended coaxial sensors. The design, analysis and performance of the stripline directional coupler in conjunction with the open-ended coaxial sensors for moisture content determination of oil palm fruits are described in detail. Simulations have been carried out to predict the variation in the reflection coefficient with moisture content in oil palm fruits. A computer program has also been developed to control the data acquisition card as well as to calculate the reflection coefficient using Agilent Visual Environment Engineering (VEE) graphical programming software. The performance of the reflectometer was tested by comparing reflection coefficient results obtained from the commercial HP4195A Network/Spectrum Analyzer. Calibration equations relating the measured reflection coefficient using the reflectometer to the moisture content found by using standard oven drying method has been established. The accuracies of the calibration equations were determined by comparing the predicted moisture content with the moisture content using standard oven drying method on 50 different fruit samples and were found to be in good agreement within 5%. The reflectometer provides a simple, fast and accurate method compared to the conventional method in monitoring the various stages of fruit ripeness.